Pancreaticoduodenectomy: Volume is not Associated with Outcome within an Academic Health Care System. (17th December 2007) - Schell, Micheal T.; Barcia, Anthony; Spitzer, Austin L.; Harris, Hobart W.
Abstract : Hypothesis . Smaller and lower-volume hospitals can attain surgical outcomes similar to high-volume centers if they incorporate the expertise and health care pathways of high-volume centers. Setting . The academic tertiary care center, Moffit-Long Hospital (ML); the community-based Mount Zion Hospital (ZION); the San Francisco County General Hospital (SFGH); and the Veterans Affairs Medical Center of San Francisco (VAMC). Patients . 369 patients who underwent pancreaticoduodenectomy between October 1989 and June 2003 at the University of California, San Francisco (UCSF) affiliated hospitals. Interventions . Pancreaticoduodenectomy. Design . Retrospective chart review. To correct for the potentially confounding effect of small case volumes and event rates, data for SFGH, VAMC, and ZION was combined (Small Volume Hospital Group; SVHG) and compared against data for ML. Main Outcome Measures . Complication rates; three-year and five-year survival rates. Results . The average patient age and health, as determined by ASA score, were similar between ML and the SVHG. The postoperative complication rate did not differ significantly between ML and the SVGH (58.8% versus 63.1% ). Patients that experienced a complication averaged 2.5 complications in both groups. The perioperative mortality rate was4 % for patients undergoing pancreaticoduodenectomy at either ML or the SVGH. Although the 3-year survival rate for patients with adenocarcinoma of the pancreas was nearly twice as high at ML (31.2% versus 18.3% at SVHG), there was no significant difference in the 5-year survival rates (19 % at ML versus18.3 % at SVHG). Conclusions . Low-volume hospitals can achieve similar outcomes to high-volume tertiary care centers provided they import the expertise and care pathways necessary for improved results.